2023
DOI: 10.1002/adhm.202300128
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Critical‐Sized Mandibular Defects Using 3D‐Printed Composite Scaffolds: A Quantitative Evaluation of New Bone Formation in In Vivo Studies

Abstract: Mandibular tissue engineering aims to develop synthetic substitutes for the regeneration of critical size defects (CSD) caused by a variety of events, including tumor surgery and post‐traumatic resections. Currently, the gold standard clinical treatment of mandibular resections (i.e., autologous fibular flap) has many drawbacks, driving research efforts toward scaffold design and fabrication by additive manufacturing (AM) techniques. Once implanted, the scaffold acts as a support for native tissue and facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 110 publications
0
1
0
Order By: Relevance
“…Given that osteogenesis is a gradual process, the degradation results suggested that membranes could act as a durable barrier in bone defects. 37,38 Due to the inherent inflexibility of pure collagen, it may not be suitable for use in GBR membranes. 39 Therefore, HA was added to enhance its mechanical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Given that osteogenesis is a gradual process, the degradation results suggested that membranes could act as a durable barrier in bone defects. 37,38 Due to the inherent inflexibility of pure collagen, it may not be suitable for use in GBR membranes. 39 Therefore, HA was added to enhance its mechanical performance.…”
Section: Discussionmentioning
confidence: 99%
“…The present surgical procedures for treating large-size bone deformities involve induced membranes, allografts, autografts, and transfer (bone). However, all the mentioned surgical procedures have drawbacks ( Bezstarosti et al, 2021 ; Dalfino et al, 2023 ). Autografts have the flaws of lack of geometry conformity, secondary morbidity, and a lack of greater graft availability.…”
Section: Gelatin-based Hydrogels Printed Formulation For Btementioning
confidence: 99%
“…That is why they are called biocomposites and biomaterials. In addition to all that has been previously mentioned, the examples of biomedical applications of CaPO 4 -containing formulations comprise regeneration of critical-sized mandibular defects [1267], orthopedic applications [401], bone revascularization [1268], bone tissue engineering [1269,1270], anti-cancer treatments [1064,1065], etc. Additionally, composite fillers composed of HA and CMC gel possess biostimulatory and skin-tightening properties that have been applied not just to the face but also to the body to boost rejuvenation [900,901].…”
Section: Biomedical and Non-biomedical Applicationsmentioning
confidence: 99%